DYNAMIC GOVERNANCE IN AGRICULTURAL SECTOR DEVELOPMENT DURING CLIMATE CHANGE ERA FOR FOOD SECURITY IN NORTH ACEH - Nurmasyahyati Nurmasyahyati; Ana Zahara; Nila Safrida; Muhaddis Muhaddis (Universitas Negeri Yogyakarta, 2026)
Climate change poses serious challenges to the agricultural sector in North Aceh through drought, flooding, and irrigation damage that reduce productivity and threaten food security. This study aims to analyze agricultural stakeholder governance using a dynamic governance (DG) approach to assess the implementation of the principles of thinking ahead, thinking again, and thinking across in responding to climate impacts. The method used is qualitative through in-depth interviews with six key informants: Bappeda, BMKG, the Agriculture and Food Service, practitioners/academics, farmers, and farmer groups. Findings show that farmers tend to rely on pragmatic adaptation strategies such as the use of water pumps, crop diversification, and simple mechanization. Meanwhile, the government focuses on macro policies, including Climate-Smart Agriculture, land expansion, and agricultural input assistance. BMKG plays a role by providing climate information and Climate Field Schools. From a DG perspective, thinking ahead is reflected in development planning, thinking again through the evaluation of farmer adaptation, but thinking across is still weak due to minimal cross-sector coordination, for example, the rehabilitation of the Krueng Pasee irrigation system, which has not been addressed. Recommendations include improving irrigation, increasing farmers' adaptation capacity, strengthening the climate information system, and establishing regular cross-sector forums to achieve adaptive and sustainable governance.